2016
DOI: 10.1002/aenm.201601198
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Graphene Tubes Decorated with FeCoNi Alloy Nanoparticles via a Template‐Free Graphitization for Bifunctional Oxygen Reduction and Evolution

Abstract: Development of highly active and stable bifunctional oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts from earth-abundant elements remains a grand challenge for highly demanded reversible fuel cells and metal-air batteries. Carbon catalysts have many advantages over others due to their low cost, excellent electrical conductivity, high surface area, and easy functionalization. However, they typically cannot withstand the highly oxidative OER environment. We report here a new class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(139 citation statements)
references
References 58 publications
6
131
0
1
Order By: Relevance
“…First, SNCF-NR provides higher ECSA. Besides, the ECSA was also estimated from the gravimetric double layer capacitance as reported by Wu et al [44,45] At a scan rate of 20 mV s −1 , the calculated value of ECSA for SNCF-NR is ≈175 m 2 g −1 , which is much higher than that for SNCF (≈74 m 2 g −1 ). We determines the ECSA through electrochemical double-layer capacitance (C dl ) measurements, as obtained by a cyclic voltammetry (CV) method ( Figure S8, Supporting Information).…”
Section: Mechanism Study: the Origin Of Enhanced Oer/her Performancementioning
confidence: 99%
“…First, SNCF-NR provides higher ECSA. Besides, the ECSA was also estimated from the gravimetric double layer capacitance as reported by Wu et al [44,45] At a scan rate of 20 mV s −1 , the calculated value of ECSA for SNCF-NR is ≈175 m 2 g −1 , which is much higher than that for SNCF (≈74 m 2 g −1 ). We determines the ECSA through electrochemical double-layer capacitance (C dl ) measurements, as obtained by a cyclic voltammetry (CV) method ( Figure S8, Supporting Information).…”
Section: Mechanism Study: the Origin Of Enhanced Oer/her Performancementioning
confidence: 99%
“…In this work, for the first time, we employed different nitrogen/carbon precursors to prepare various Fe‐N‐C catalysts with an aim to tuning catalyst morphology and structure, which will further link with catalyst activity and stability. Among available precursors, three often studied, that is, polyaniline (PANI), dicyandiamide (DCDA), melamine (MLMN), were identified to be effective to yield sufficient ORR catalytic activity. Although these precursors have been investigated individually, a comparative study of catalyst morphology and performance from various binary combinations under similar reaction conditions has not been done yet.…”
Section: Introductionmentioning
confidence: 98%
“…[103,104] Goodenough et al demonstrate excellent performance of NiCo nanoparticles anchored on porous fibrous carbon aerogels (NiCo/PFC aerogels) as bifunctional ORR/ OER catalysts, as shown in Figure 11c. [103] This material is designed and synthesized using K 2 Ni(CN) 4 /K 3 Co-(CN) 6 -chitosan hydrogel as processors.…”
Section: (Alloyed)metal/n-doped Carbonmentioning
confidence: 99%
“…Wu et al further reported ultralarge sized N doped graphene tubes (N-GTs) (>500 nm) decorated with FeCoNi alloy particles for bifunctional ORR/OER. [104] These tubes are prepared from an inexpensive precursor, dicyandiamide, via a template free graphitization process. The ORR/OER activity and the stability of these graphene tube catalysts depend strongly on the transition metal precursors.…”
Section: (Alloyed)metal/n-doped Carbonmentioning
confidence: 99%